PENGARUH LATIHAN CIRCUIT TRAINING (LATIHAN SIRKUIT) TERHADAP DAYA TAHAN TIM SEPAKBOLA SMPN 29 PEKANBARU - Ardinata, Rozi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. Issues raised in this research is the player often exhausted in the running after a ball or chase opponents, in a tournament or a test match, the team always defeat is because the durability of the players who have not been so good, most of the players can not finish the game 2x45 minutes consequently, the players had cramps and unusual resume the game. Form of research with experimental (Experimental), with a population of soccer player SMP 29 Pekanbaru, the data in this study is the entire population of 16 people. The instruments are made in the study is a test run of 2.4 km, which aims to measure the durability. After the data is processed with statistical, normality test to test the extent signifikat lilifor 0,05a. The hypothesis is the effect of exercise circuit training (circuit training) against resistance. Based on t test analysis produces T calculated at 7,77 and amounted to 1,764 T table T Mean arithmetic> T table. Based on the analysis of statistical data, then the data is normal. Thus the effects of exercise circuit training (circuit training) against the football team durability SMP 29 Pekanbaru.Keywords : effects of exercise circuit training (circuit training) against Endurance